A morphometric and population genetic investigation of Opuntia engelmannii Salm-Dyck (Cactaceae: Opuntioideae) lineage variation in Africa - Mbonani, Siphosenkosi (My University, 2019)
Opuntia engelmannii, commonly known as ‘small round-leaved prickly pear’ is native to the Americas (North, Central and South America) but is highly invasive in South Africa and Kenya. Moreover, it is a priority for biological control in South Africa as it is NEM:BA category 1b invader. Different O. engelmannii found in different geographic locations in South Africa and Kenya are variable in their morphology and are hypothesized to be genetically different. Dactyolopius opuntiae has been used in South Africa to control invasive cactus for over 80 years and has been considered a successful biocontrol agent on some Opuntia species. The success of O. engelmannii biological control will depend on D. opuntiae biotype compatibility to O. engelmannii genetic diversity and on the insects host specificity in both countries. Firstly, we investigated the validity of observed morphological differences among O. engelmannii lineages and a sister taxon, O. stricta. Morphological data were used to test the extent of variability among lineages to see which lineages differ morphologically. Diagnostic characters such as spine, cladode, areole and fruit were compared among the lineages to quantify these observed differences. A Principal Component Analysis (PCA) of spine morphology showed that the Limpopo and Kenyan lineage are most similar, while the Eastern Cape (spines) is more similar to O. stricta. The Northern Cape lineage is different in its spine morphology to all the other O. engelmannii lineages, but it is also different to O. stricta. Furthermore, a Nonmetric MultiDimension Scaling (NMDS) of morphology data showed that spine morphology, more than cladode, areole and fruit morphology is a more useful diagnostic character to confirm O. engelmannii lineage identity. Secondly, we investigated genetic structure and differentiation among the lineages to complement the morphological data. The results showed that Eastern Cape (spineless), Limpopo and Kenyan lineages had less genetic differentiation among them (FST < 0.05), and are therefore genetically similar to each other. The Eastern Cape (spines) lineage was genetically differentiated from the other O. engelmannii lineages (FST 0.05 — 0.15) and it was genetically similiar to the O. stricta population. Moreoever, we found that these observed genetic differences are not because of the geographical locations of the putative lineages, therefore refuting the isolation by distance hypothesis. There is some congruency between morphology and molecular identity, the morphometric NMDS and the molecular data PCoA both suggest that the Eastern Cape (spines) is more similar to the O. stricta lineage than the other O. engelmannii lineages. Both morphometric and molecular data lead to a better understanding of the underlying reasons for successful biocontrol of Opuntia using cochineal insects. The Eastern Cape (spines) lineage is more similar to the plant lineage (O. stricta) on which the D. opuntiae ‘stricta’- biotype is an effective biocontrol agent. The use of D. opuntiae ‘stricta biotype’ might be effective in the control of the Eastern Cape (spines) population because both plant lineages have a similar genetic structure. A new ‘biotype’ of D. opuntiae, that has not been released in South Africa was recently collected from the USA. It has successfully established in quarantine where it has shown a high reproductive output on the Kenyan lineage of O. engelmannii. Since there is a little genetic differentiation between the Kenyan and the Limpopo lineage, the same insect biotype could potentially be used to successfully control both the Kenyan and Limpopo lineages.
This dissertation is submitted to the Faculty of Science, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in the School of Animal, Plant and Environmental Science, 2019